The Role of the Women's Empowerment and Child Protection Service in Assuring the Rights of Children as Victims of Sexual Intercourse in South Central Timor District - Arjuna Putra Pamungkas (Jurnal Restorasi : Hukum dan Politik, 2023)
The large number of cases of sexual intercourse with children where the rights of the child who is the victim of sexual intercourse are not fulfilled. This study aims to determine the role of the Office of Women's Empowerment and Child Protection in guaranteeing the rights of children as victims of sexual intercourse in the South Central Timor District, and to find out the Obstacles of the Office of Women's Empowerment and Child Protection in guaranteeing the fulfillment of the rights of children as victims of sexual intercourse in the South Central Timor District. The research method used in this research is juridical-empirical legal research which is related to the research problem under study. The legal sources and materials used are primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show that the fulfillment of the rights of children who are victims of sexual intercourse in the South Central Timor district by the Office of Women's Empowerment and Child Protection of South Central Timor District, but there are several obstacles encountered in the process of fulfilling the rights of children as victims of sexual intercourse.It is suggested that the Office of Women's Empowerment and Child Protection of the South Central Timor Regency can carry out an evaluation in overcoming the obstacles that have so far been encountered in carrying out the task of fulfilling the rights of children who are victims of sexual intercourse in the South Central Timor Regency area.